2018
DOI: 10.1016/j.jsps.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of children poisoning cases in community teaching hospital in Riyadh, Saudi Arabia

Abstract: The results found that the majority of poisoning cases occurred in children under the age of six and required only observation without treatment. These results necessitate the need for close cooperation between different governmental health-sectors to establish national epidemiological surveillance of poisoning events in Saudi Arabia to help to develop national plans to decrease the financial burden of emergency department congestion and hospital crowding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 16 publications
(26 reference statements)
12
43
0
Order By: Relevance
“…Several studies of acute pediatric poisoning have been conducted in Saudi Arabia [ 26 , 27 , 28 , 29 , 30 ]. A review by Izuora and Adeoye (2001) in Hafr Al Batin of seven years of case notes of children admitted to a single military hospital in the Eastern Province identified 168 accidental pediatric poisonings out of 9951 pediatric admissions (1.7%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies of acute pediatric poisoning have been conducted in Saudi Arabia [ 26 , 27 , 28 , 29 , 30 ]. A review by Izuora and Adeoye (2001) in Hafr Al Batin of seven years of case notes of children admitted to a single military hospital in the Eastern Province identified 168 accidental pediatric poisonings out of 9951 pediatric admissions (1.7%).…”
Section: Introductionmentioning
confidence: 99%
“…Children younger than two years of age (n = 459, 62%) were significantly affected by poisoning. Drug overdose (n = 119, 92.2%) was the major cause of poisoning and analgesics were the most commonly reported medicine (n = 26, 20.4%) [ 29 ]. They concluded with a recommendation, “to help to develop national plans to decrease the financial burden of emergency department congestion and hospital crowding” [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering unintentional intoxication, in research carried out in other countries, it is noticed that the ingestion of drugs is the main cause of accidental intoxication in children, as in Saudi Arabia where 70% of the exogenous intoxications were caused by drugs (Alghadeer et al, 2018) and in Taiwan 41.4% corresponded to drug intoxications (Lee et al, 2019). Drug intoxications that occurred in children have multifactorial causes and are generally related to specific conditions of each culture and region (Alghadeer et al, 2018). In relation to the age group of children up to 10 years, patterns similar to the results of our study of accidental intoxication were found in other Brazilian cities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that Wnt/βcatenin signal pathway plays a role in the pathogenesis and progression of liver diseases [7] . The studies on the expression and clinical significance of Wnt5a, β-catenin, E-cadherin in hepatocellular carcinoma indicated that the expression of Wnt5a is negatively correlated with the clinical stage and prognosis of liver cancer, and can exert significant antioncogenic effect on tumor tissues [8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%